Modern Methods for Interrogating the Human Connectome. (18th February 2016) - Lowe, Mark J.; Sakaie, Ken E.; Beall, Erik B.; Calhoun, Vince D.; Bridwell, David A.; Rubinov, Mikail; Rao, Stephen M.
Abstract: Objectives: Connectionist theories of brain function took hold with the seminal contributions of Norman Geschwind a half century ago. Modern neuroimaging techniques have expanded the scientific interest in the study of brain connectivity to include the intact as well as disordered brain.Methods: In this review, we describe the most common techniques used to measure functional and structural connectivity, including resting state functional MRI, diffusion MRI, and electroencephalography and magnetoencephalography coherence. We also review the most common analytical approaches used for examining brain interconnectivity associated with these various imaging methods.Results: This review presents a critical analysis of the assumptions, as well as methodological limitations, of each imaging and analysis approach.Conclusions: The overall goal of this review is to provide the reader with an introduction to evaluating the scientific methods underlying investigations that probe the human connectome. ( JINS, 2016, 22, 105–119)